2020
DOI: 10.1109/tte.2020.3001042
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Robust Design of Active Disturbance-Rejection Current Controller for Permanent Magnet Machines in Transportation Systems

Abstract: The excellent steady state and dynamic performance are also required. Therefore, high-performance PMSM control in the focus of comprehensive research during the last decades, and still continues to receive a great attention from the researchers.The most established control strategy for PMSMs consists of cascaded control loops, typically with an inner loop for current regulation and an outer loop for speed control. It can be argued that the current control loop has a major effect on the overall system performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For an electrical generator for high-speed applications, the electrical parameters are relatively small. For example, for the AEGART electrical machine developed under the frame of the Clean Sky project [26], the stator resistance and inductance are 1.058 mΩ and 100 μH, respectively [38]. Such a small impedance causes the motor current to change quickly, resulting in difficulty for discrete digital control.…”
Section: B Potential Challenges From the Down-scale Lab Prototype To A Full-scale Systemmentioning
confidence: 99%
“…For an electrical generator for high-speed applications, the electrical parameters are relatively small. For example, for the AEGART electrical machine developed under the frame of the Clean Sky project [26], the stator resistance and inductance are 1.058 mΩ and 100 μH, respectively [38]. Such a small impedance causes the motor current to change quickly, resulting in difficulty for discrete digital control.…”
Section: B Potential Challenges From the Down-scale Lab Prototype To A Full-scale Systemmentioning
confidence: 99%
“…4. Based on the ADRC principle [23,24], it is assumed that the external disturbances and the process dynamics are represented as a total disturbance. Subsequently, the voltage equations of the PMSM model can be written such as:…”
Section: Active Disturbance Rejection Controlmentioning
confidence: 99%
“…The MPC cost function is given by [27,29]: 24) subject to a discrete state-space model in ( 22) and ( 23), where ( ) 3 * 1 = ( ) 3 * 1 − ( ) 3 * 1 is the error, ( ) 3 * 1 is the system output, ( ) 3 * 1 is the reference input, ( ) 2 * 1 is the system control input, Q( ) 3 * 3 and R( ) 2 * 2 are weighting matrices, ny is the prediction horizon value and nu is the control horizon value. The model could be used recursively to find the predictions over the prediction horizon ny as follows:…”
Section: Model Predictive Controlmentioning
confidence: 99%
“…It can be argued that the current control loop has a major effect on the overall system performance [1]. Therefore, many studies that investigate various current control schemes are reported in [2][3][4][5]. The hysteresis controller, for instance, can achieve instantaneous tracking of the reference.…”
Section: Introductionmentioning
confidence: 99%